2006
DOI: 10.1161/circulationaha.105.537415
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Predictors of Incident Congestive Heart Failure and All-Cause Mortality in Postmenopausal Women

Abstract: Background-Information is limited about ECG predictors of the risk of incident congestive heart failure (CHF), particularly in women without overt manifestations of cardiovascular disease (CVD). Methods and Results-We evaluated hazard ratios for incident CHF and all-cause mortality using Cox regression in 38 283 participants of the Women's Health Initiative (WHI) during a 9-year follow-up. All risk models were adjusted for demographic and available clinical and therapeutic variables (multivariable-adjusted mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 40 publications
1
97
0
1
Order By: Relevance
“…This index is not sensitive to subjective definition of the end of the T-wave and is therefore a reproducible and reliable index of cardiac repolarisation. This index was recently described to be a powerful predictor of mortality in various populations [12][13][14][15][16]. TCRT values tended to be more abnormal (smaller) in diabetic patients, even when glucose levels were normal and the abnormality became more marked during hypoglycaemia, suggesting that hypoglycaemia further increases the heterogeneity in global repolarisation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This index is not sensitive to subjective definition of the end of the T-wave and is therefore a reproducible and reliable index of cardiac repolarisation. This index was recently described to be a powerful predictor of mortality in various populations [12][13][14][15][16]. TCRT values tended to be more abnormal (smaller) in diabetic patients, even when glucose levels were normal and the abnormality became more marked during hypoglycaemia, suggesting that hypoglycaemia further increases the heterogeneity in global repolarisation.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, novel repolarisation analyses have been developed to evaluate the characteristics of cardiac repolarisation with greater accuracy. New descriptors of T-wave morphology and the spatial QRS-T angle have already been shown to have better prognostic values than QT interval or QT dispersion with regard to cardiac events in several populations [12][13][14][15][16] and increased complexity of ventricular repolarisation measured by principal component analysis of T-wave morphology has been found to distinguish patients with congenital long QT syndrome from unaffected participants [17,18]. Therefore, we decided to study the effects of controlled insulininduced hypoglycaemia on the T-wave loop and the QRS complex loop in type 1 diabetic patients and age-matched non-diabetic control participants.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports have shown that findings on the routine ECG are associated with future HF events,8, 9, 10, 11, 12, 13, 14, 15, 16, 17 few have explored whether ECG predictors vary in their ability to distinguish between HFrEF and HFpEF. A recent examination from the Framingham Heart Study has shown that left ventricular hypertrophy and left bundle‐branch block are associated with HFrEF and that atrial fibrillation is associated with HFpEF 28.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive analysis of 12 ECG variables in 38,283 women participating in the Women's Health Initiative found repolarization disorders, signs of MI, and QRS abnormalities to be equally predictive of coronary heart disease morbidity and mortality (11). Repolarization disorders and infarction pattern were also predictors of incident congestive heart failure and all-cause mortality (12). Finally, in atrial fibrillation trials, the preservation of sinus rhythm was associated with a considerable reduction in the risk of death (13,14).…”
Section: Discussionmentioning
confidence: 99%